Scaling the plasma focus for fusion energy considerations - Saw, Sor Heoh; Lee, Sing (Wiley Online Library, 2011)
Using the Lee model code for dense plasma focus, series of numerical experiments were systematically carried out to determine the scaling of bank energies with total current and focus pinch current and the scaling of neutron yields with energies and currents. The numerical experiments were carried out over a range of bank energies from 8 kJ extending up to 24MJ on the PF1000 and a proposed less damped modern bank. It also includes a study on the effects of increasing bank energies by increasing bank charging voltage and capacitance of the bank for a practical optimum plasma focus machine. The results provide convincing data to show that it is possible to scale up the plasma focus machine at just 3MJ for D-D neutron yield of 1013 per shot and 1015 neutrons per shot when it is converted to operate in D-T. Copyright r 2010 John Wiley & Sons, Ltd.